The Impact of Tourism Development on Culture in the Digital Age Case Study : Saung Angklung Udjo - Ila Rahma Cahayani; Trixie Pavella Boli (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study analyzes the impact of digital-era tourism on cultural preservation, using Saung Angklung Udjo (SAU) in Bandung, West Java, as a case study. While the digital era offers wide access to information, it also poses challenges to the authenticity and sustainability of local culture. The angklung, as a traditional art form, faces the threat of extinction and declining interest from the younger generation. As a cultural tourist destination, SAU has successfully preserved the angklung through digital transformation, which was accelerated by the COVID-19 pandemic. The research used a descriptive qualitative approach, with data collected through literature and documentation studies. The findings indicate that SAU functions as a center for cultural preservation, education, and local community empowerment. SAU's digitalization strategy includes leveraging social media (especially Instagram) for promotion, education, and information dissemination, with a focus on creating unique and informative Sundanese cultural content. The positive impacts of this digitalization include global cultural promotion, increased youth participation, easier access to information, innovation in cultural attractions, a solution during times of crisis, and the creation of new jobs in the digital cultural sector. However, there are also negative effects, such as the potential for excessive commodification that may reduce the sacred value of the culture, the inability of online experiences to fully replace direct interaction, and the risk of plagiarism and content misuse. The study concludes that digitalization is an effective tool for SAU in promoting and educating about culture, despite the ongoing challenges of commodification and the erosion of authentic values. Through a strategy of cultural content, local community engagement, and interactive performances, SAU has successfully balanced preservation and innovation, making it a model for cultural tourism adaptation in the digital age.